Modeling of LTO approach time-in-mode values in MATLAB using the generalized extreme value distribution - Bo Stloukal; Ivan Nagy (Acta Polytechnica CTU Proceedings)
The landing and take-off (LTO) cycle, which is used to calculate emissions of aircraft below 3 000 feet, consists of four operating modes, each of which has a standardized time duration or time-in-mode (TIM). In this paper, we model TIM values of the Approach operating mode for two aircraft types (Boeing 737-800 and Airbus A320) arriving on Runway 24 at Prague Václav Havel Airport using the generalized extreme value (GEV) distribution. Predictions of the TIM values are made using the models, and the performance of each model is evaluated. The results show that for both aircraft types, the predicted TIM values lead to total emissions estimates deviating on average by 1 to 2 percent from estimates made using the real TIM values, showing good model performance. The presented approach is also shown to be beneficial in comparison with using the standard TIM value (240 s), highlighting the feasibility of further research in this area as one of the avenues of improving the LTO cycle methodology.